DOMESTIKASI DAN PEMATANGAN GONAD IKAN TAPAH (Wallago sp) DARI PERAIRAN SUNGAI KAMPAR, RIAU - Yurisman Yurisman; Sukendi Sukendi; Ridwan Manda Putra (Fakultas Perikanan dan Kelautan, Universitas Riau, 2010)
A study aims to find out a domestication and gonad maturationtechnique of Wallago sp captured in the Kampar River, Riau has benn conductedon May to Nopember 2009. Fish samples were kept in 1 x 2 x 1.5 m cages, 6fishes/cages. The fishes were treated with three types of food. Results shown thatWallago domestication can be conducted by rearing the fish for 4 weeks. Theproper food for the fishes are sinking pellet 888-S (4) (P3), floating pellet CPPP781 (P2), and floating pellet T 79 – 3P (PI). The total growth rate , total lengthand daily growth rate of treated fish are 647.77 gr; 9.3933 cm and 0.320 % for P3;426.67 gr; 6.8367 cm and 0.226 % for P2 and 353.34 gr; 6.00 cm and 0.1911 %for P1. However, there are only 1st and 2nd gonad maturity level obtained in thetreated fishes. Survival rate of the fishes in 100 %.